Implementasi Kurikulum Berbasis Entrepreneurship di SMA Negeri 1 Ingin Jaya Aceh Besar - Hidayatullah, Alfian; Maysa, Saifullah (FITRAH: International Islamic Education Journal, 2024)
With the advancement of technology and globalization, educational institutions are increasingly required to implement entrepreneurship education programs to address issues such as unemployment and limited job opportunities. One of the educational institutions that has adopted an entrepreneurship-based curriculum is SMA Negeri 1 Ingin Jaya Aceh Besar. This school has significant potential for implementing entrepreneurship programs, supported by adequate internal resources, including human resources, facilities, and infrastructure. The objective of this study is to analyze the implementation of the entrepreneurship-based curriculum at SMA Negeri 1 Ingin Jaya Aceh Besar. This research employs a descriptive qualitative approach, with subjects including the school principal, entrepreneurship guidance teachers, and students. Data were collected through observation, in-depth interviews, and documentation. The results indicate that the implementation of the entrepreneurship curriculum follows three main stages: planning, implementation, and evaluation of learning. Each stage shows significant adaptation and development in response to the needs and conditions of the school. The findings highlight the importance of internal school support in the successful implementation of the entrepreneurship curriculum. Abstrak Seiring dengan perkembangan teknologi dan globalisasi, lembaga pendidikan semakin dituntut untuk menyelenggarakan program pendidikan kewirausahaan guna mengatasi masalah pengangguran dan terbatasnya lapangan kerja. Salah satu satuan pendidikan yang menerapkan kurikulum kewirausahaan adalah SMA Negeri 1 Ingin Jaya Aceh Besar. Sekolah ini memiliki potensi besar dalam implementasi kewirausahaan, didukung oleh sumber daya internal yang memadai, baik dari aspek sumber daya manusia maupun sarana dan prasarana. Penelitian ini bertujuan untuk menganalisis implementasi kurikulum berbasis kewirausahaan di SMA Negeri 1 Ingin Jaya Aceh Besar. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan subjek penelitian terdiri dari kepala sekolah, guru pembimbing kewirausahaan, dan siswa. Data dikumpulkan melalui teknik observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi kurikulum kewirausahaan dilakukan melalui tiga tahapan utama: perencanaan, pelaksanaan, dan evaluasi pembelajaran. Setiap tahapan menunjukkan adanya adaptasi dan pengembangan yang mendalam sesuai dengan kebutuhan dan kondisi sekolah. Temuan ini mengindikasikan pentingnya peran dukungan internal sekolah dalam keberhasilan implementasi kurikulum kewirausahaan.